Appeals of Communism - Almond, Gabriel A. (Gabriel Abraham), 1911-2002 (Book collections on Project MUSE., 1954)
This study, based on an extensive program of interviewing former American, British, French, and Italian Communists, provides many answers to these questions and gives a convincing insight into the motivations, tensions, and loyalties of Party members. First, the book examines Communist literature (the Lenin and Stalin classics and current Party media) to see what the Communists themselves expect of their movement. Then it shows whether this ideal is realized by the people who have "been through it." The final sections, which follow the interviews closely, reveal what actually happens to people when they join, while they are in the Party, and after they leave. Originally published in 2050.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.